A dictionary of British and Irish history - Peberdy, Robert; Waller, P. J. (Philip J.) (Hoboken : Wiley, 2020)
"The Dictionary of British and Irish History is a source of concise and basic information about all periods of prehistory and history for all parts of the British Isles. It provides accounts of events, definitions of terms, biographies, and overviews of major topics. Organized by alphabetically ordered headwords, it is designed both to provide instantly required information and to encourage wider learning through the careful interrelationship of entries and the provision of extensive cross-referencing. A major feature is the way it deals even-handedly with the component parts of Britain and with Ireland, often through comparable entries. The editors intend that the Dictionary will provide readers with the essentials of subjects rapidly and clearly, so that they can then tackle more detailed and discursive publications"--
BIBINDX
Keywords: Great Britain -- History -- Encyclopedias; Ireland -- History -- Encyclopedias; Electronic books; Encyclopedias; History; Dictionaries; Encyclopedias